Effects of Paraquat on Behavior, Morphology, Mortality, and Acetylcholinesterase Expression in Red Tilapia Fingerlings - Thanomsit, Chutima; Wattanakornsiri, Amnuay; Prasatkaew, Witchuda; Nanuam, Jakkaphun; Jutagate, Tuantong; Mongkolvai, Patcharee; Saetiew, Jadsada; Meemon, Panomsak; Nanthanawat, Phochit (Agriculture and Natural Resources, 2025)
Importance of the work: Fish can be exposed to pesticides, which poses risks and may have cascading effects on consumers. Herbicides used in agriculture can leak into aquatic environments, causing harmful effects on fish. While some effects on tilapia have been documented, insights into aspects such as gene expression remain unreported. Objectives: This study investigates the effects of paraquat exposure on red tilapia (Oreochromis niloticus × O. mossambicus) fingerlings, focusing on mortality, behavioral and morphological alterations, and acetylcholinesterase (AChE) expression. Materials and Methods: Red tilapia fingerlings were subjected to acute toxicity assessment by exposing them to varying concentrations of paraquat (0, 2.76, 5.52, 8.28, and 11.04 mg/L) for 24, 48, 72, and 96 h. AChE expression was analyzed via SDS-PAGE and Western blotting, and morphological changes were investigated using light microscopy and optical coherence tomography (OCT) to assess the effects of paraquat on the fingerlings. Results: Cumulative mortality increased with paraquat concentration and exposure duration. Behavioral abnormalities, such as loss of equilibrium and abnormal swimming patterns, were most severe at higher paraquat concentrations and with longer exposure durations. Morphological damage, including wounds and scale loss, worsened with increased exposure. AChE expression in gill tissues decreased over time, indicating neurotoxic effects on the fish’s nervous system. OCT was more effective than traditional light microscopy in detecting early-stage morphological changes, providing detailed insights into tissue damage. Main finding: This study underscores the urgent need for stricter herbicide regulations to protect aquatic ecosystems. The findings provide critical insights into paraquat's impact on aquatic life and highlight the importance of strategies to manage contamination, mitigate risks to consumers, and reduce potential health threats posed by paraquat accumulation in the food chain.